Blurring Realities : The fusion of real and Virtual in The Art World - Auzani Zeda, Mohamed Kassim (UNIMAS Publisher, 2025)
The emergence of technology has had a significant impact on our everyday lives. The concept of immersive environments has gained much popularity in this rapidly changing technological environment that we live in today. Emerging technologies also provide artists with new approaches to creating and manipulating art, allowing audiences to engage in immersive environments. However, what does it entail - being in an immersive environment?